2006
DOI: 10.1080/10242690500369199
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between External Debt, Defence Expenditures and GNP Revisited: The Case of Turkey

Abstract: This paper extends the Looney and Frederiksen (1986) study and investigates the relationship among external debt, defence expenditures and GNP in Turkey for 1960-2002. After applying cointegration analysis of a multivariate system of equations, impulse response functions and variance decomposition are estimated. The impulse response functions indicate that defence expenditures have a positive effect on external debt stock. Moreover, impulse response of GNP to defence expenditures tended to hike slightly within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
29
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(41 citation statements)
references
References 11 publications
7
29
0
5
Order By: Relevance
“…The aim of present paper is to investigate the relationship between military spending and and unreliable empirical results due to sharpness in time series in developing economies (Karagol, 2006). In such situation, use of log-linear specification is better option for time series analysis and it directly produces elasticity.…”
Section: Modeling and Justifications For The Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…The aim of present paper is to investigate the relationship between military spending and and unreliable empirical results due to sharpness in time series in developing economies (Karagol, 2006). In such situation, use of log-linear specification is better option for time series analysis and it directly produces elasticity.…”
Section: Modeling and Justifications For The Variablesmentioning
confidence: 99%
“…An increase in debt services is linked with high level of external debt which restricts investment and capital formation that in turn slows down the rate of economic growth. Further, the level of external capital is decreased due to heavy payments of foreign reserves (through exports) on external debt that further reduces the creditworthiness of an economy (Karagol, 2002) which has inverse impact on liquidity of debtor countries and limit their capacity to fulfill other national commitments (Karagol, 2006). Repayment of debt with heavy debt servicing has become serious problem both for developing and less developed economies of the globe now-a-days.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Military expenditures may also lead to improvements in infrastructure while a similar positive effect is also postulated when it comes to the labour force and the technical skills acquired during military training that can then be useful endowments for the civilian life of soldiers once decommissioned (MacNair et al, 1995). On the other hand, however, there has been ample evidence generated by a plethora of studies pointing to a negative impact on growth using both cross-section as well as time series data-sets in the empirical investigation of the issue at hand (inter alia: Deger and Smith, 1983;Lim, 1983;Faini et al, 1984;Fredericksen and Looney, 1983;Birdi and Dunne, 2002;Karagol and Palaz, 2004;Karagol, 2006;Mylonidis, 2008;Smith and Tuttle, 2008;Pieroni, 2009;Abu-Qarn, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Karagol and Palaz(2004) revealed the existence of a uni-directional causality relationship running from military expenditure to economic growth in Turkey in the short run only. However, the findings by Karagol (2006) suggested an indirect negative impact of military expenditure on economic growth through increasing external debt stock in Turkey. The same study by Karagol (2006) also found out that military spending had a huge negative impact on economic growth within the first two years and faded thereafter in Turkey.…”
Section: Review Of Related Literaturementioning
confidence: 94%